EFEKTIFITAS BIMBINGAN IBU HAMIL TENTANG DETEKSI DINI TANDA BAHAYA PADA IBU DENGAN MEDIA LEAFLET DAN AUDIO VISUAL - NiGusti Made Ayu Agung Budhi; Titi Nurhayati (Poltekkes Kemenkes Bandung, 2020)
This study aims to determine the effectiveness of guidance in pregnant women about the early detection of danger signs of pregnancy, childbirth and childbirth using leaflets and audio visual media. The research design was a quasi-experimental, non-randomized pretest-posttest with two group design models. The subjects of this study were normal pregnant women with gestational age> 28 weeks with a large sample of 32 people. This study compared the mean difference between the two intervention groups, namely those who used audiovisual media and leaflet media in providing guidance for early detection of danger signs for women during pregnancy, childbirth and the puerperium. The results of the pretest and posttest in this study were tested by non-parametric test with Wilcoxon rank test and Mann-withney. The results of this study found that the characteristics of the respondents most of the healthy reproductive age, low education level, have health insurance and have a good pregnancy check. The results show that both audiovisual media and leaflet media can increase the knowledge of pregnant women about early detection of danger signs of pregnancy, childbirth and puerperium with a value of p <0.05. Obtained guidance through Lieflet is not significant to changes in attitudes of pregnant women with a p value> 0.05, but through audio visual guidance affects positive changes in maternal attitudes with a value of p <0.05. In conclusion, audiovisual media is very effective in increasing knowledge and changing attitudes of mothers towards early detection of danger signs of pregnancy, childbirth and postpartum compared to lieflet media.